2018
DOI: 10.1186/s13256-018-1657-4
|View full text |Cite
|
Sign up to set email alerts
|

Wernekink commissure syndrome with palatal myoclonus at onset: a case report and review of the literature

Abstract: BackgroundWernekink commissure syndrome causes a peculiar combination of internuclear ophthalmoplegia, dysarthria, and delayed-onset palatal myoclonus. Palatal myoclonus is thought to be secondary to delayed hypertrophic degeneration of the bilateral inferior olivary nuclei secondary to involvement of bilateral dentatoolivary tract. We describe a case of a patient with early-onset palatal myoclonus.Case presentationA 53-year-old Caucasian man with several vascular risk factors presented to our emergency room w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Other findings that have been frequently reported in WCS are ophthalmoplegia and nystagmus [3,5,10]. In their study, Zhou et al reported that in 12 patients with caudal paramedian midbrain infarction, diplopia and internuclear ophthalmoplegia (INO) were frequently seen [11].…”
Section: Discussionmentioning
confidence: 93%
“…Other findings that have been frequently reported in WCS are ophthalmoplegia and nystagmus [3,5,10]. In their study, Zhou et al reported that in 12 patients with caudal paramedian midbrain infarction, diplopia and internuclear ophthalmoplegia (INO) were frequently seen [11].…”
Section: Discussionmentioning
confidence: 93%
“…Traktus dentato-rubro-olivary yang turun menghubungkan dentate dan inti sela otak kecil dengan inti merah kontralateral melalui batang otak superior dan nukleus olivari inferior di medula. Lesi pada commissure Wernekink di cauda midbrain dapat merusak jalur dentato-rubrothalamic atau dentato-rubro-olivary, yang masing-masing menyebabkan tremor Holmes dini atau tertunda dan myoclonus palatal atau tremor onset tertunda (Mullaguri, Battineni, & Chuquilin, 2018).…”
Section: Hasil Dan Diskusiunclassified
“…Wernekink commissure syndrome is a rare syndrome , due to involvement of the midbrain and it is characterized by bilateral cerebellar ataxia, internuclear ophthalmoplegia and delayed onset palatal myoclonus. [1][2][3] The structures located in the medial part of midbrain include oculomotor nuclei, descending cerebellar tracts, medial longitudinal fasciculus, and central tegmental tract, and a lesion in this region can result in the clinical features described in this syndrome. 4 Wernekink commissure syndrome was first described by Lhermitte and it was named after German anatomist Friedrich Wernekink, who described it as a horseshoe-shaped commissure.…”
Section: Introductionmentioning
confidence: 99%